Estradiol and selective estrogen receptor agonists differentially affect brain monoamines and amino acids levels in transitional and surgical menopausal rat models. (1st October 2019) - Long, Tao; Yao, Jeffrey K.; Li, Junyi; Kirshner, Ziv Z.; Nelson, Doug; Dougherty, George G.; Gibbs, Robert B.
Abstract: Estrogens have many beneficial effects in the brain. Previously, we evaluated the effects of two models of menopause (surgical vs. transitional) on multiple monoaminergic endpoints in different regions of the adult rat brain in comparison with levels in gonadally intact rats. Here we evaluated the effects of estrogen receptor (ER) agonist treatments in these same two models of menopause. Neurochemical endpoints were evaluated in the hippocampus (HPC), frontal cortex (FCX), and striatum (STR) of adult ovariectomized (OVX) rats and in rats that underwent selective and gradual ovarian follicle depletion by daily injection of 4-vinylcyclohexene-diepoxide (VCD), after 1- and 6-weeks treatment with 17β-estradiol (E2), or with selective ERα (PPT), ERβ (DPN), or GPR30 (G-1) agonists. Endpoints included serotonin (5-HT) and 5-Hydroxyindoleacetic acid, dopamine (DA), 3, 4-Dihydroxyphenylacetic acid and homovanillic acid, norepinephrine (NE) and epinephrine, as well as the amino acids tryptophan (TRP) and tyrosine (TYR). Significant differences between the models were detected. OVX rats were much more sensitive to ER agonist treatments than VCD-treated rats. Significant differences between brain regions also were detected. Within OVX rats, more agonist effects were detected in the HPC than in any other region. One interesting finding was the substantial decrease in TRP and TYR detected in the HPC and FCX in response to agonist treatments, particularly in OVX rats. This is on top of the substantial decreases in TRP and TYR previously reported one week after OVX or VCD-treatments in comparison with gonadally intact controls. Other interesting findings included increases in the levels of 5-HT, DA, and NE in the HPC of OVX rats treated with DPN, increases in DA detected in the FCX of OVX rats treated with any of the ER agonists, and increases in 5-HT and DA detected in the STR of OVX rats treated with E2. Many effects that were observed after 1-week of treatment were no longer observed after 6-weeks of treatment, demonstrating that effects were temporary despite continued agonist treatment. Collectively, the results demonstrate significant differences in the effects of ER agonists on monoaminergic endpoints in OVX vs. VCD-treated rats that also were brain region-specific and time dependent. The fact that agonist treatments had lesser effects in VCD treated rats than in OVX rats may help to explain reports of lesser effects of estrogen replacement on cognitive performance in women that have undergone transitional vs. surgical menopause. Highlights: Used two clinically relevant models of menopause (surgical vs transitional). Compared effects of estradiol and selective estrogen receptor agonists on neurochemical markers in rat brain. Detected effects on dopaminergic, serotoninergic and noradrenergic endpoints, and levels of tyrosine and tryptophan. Effects were agonist specific, model- and time-dependent, and differed between brain-regions. Agonist treatments had lesser effects in VCD-treated rats than in OVX rats.